Pulmonary Hypertension in Connective Tissue Diseases Other than Systemic Sclerosis - Budhram, Brandon; Weatherald, Jason; Humbert, Marc (Seminars in Respiratory and Critical Care Medicine, 2024)
Pulmonary hypertension (PH) is a known complication of certain connective tissue diseases (CTDs), with systemic sclerosis (SSc) being the most common in the Western world. However, PH in association with non-SSc CTD such as systemic lupus erythematous, mixed connective tissue disease, and primary Sjögren's syndrome constitutes a distinct subset of patients with inherently different epidemiologic profiles, pathophysiologic mechanisms, clinical features, therapeutic options, and prognostic implications. The purpose of this review is to inform a practical approach for clinicians evaluating patients with non-SSc CTD-associated PH.The development of PH in these patients involves a complex interplay between genetic factors, immune-mediated mechanisms, and endothelial cell dysfunction. Furthermore, the broad spectrum of CTD manifestations can contribute to the development of PH through various pathophysiologic mechanisms, including intrinsic pulmonary arteriolar vasculopathy (pulmonary arterial hypertension, Group 1 PH), left-heart disease (Group 2), chronic lung disease (Group 3), chronic pulmonary artery obstruction (Group 4), and unclear and/or multifactorial mechanisms (Group 5). The importance of diagnosing PH early in symptomatic patients with non-SSc CTD is highlighted, with a review of the relevant biomarkers, imaging, and diagnostic procedures required to establish a diagnosis.Therapeutic strategies for non-SSc PH associated with CTD are explored with an in-depth review of the medical, interventional, and surgical options available to these patients, emphasizing the CTD-specific considerations that guide treatment and aid in prognosis. By identifying gaps in the current literature, we offer insights into future research priorities that may prove valuable for patients with PH associated with non-SSc CTD.
Keywords: pulmonary hypertension; pulmonary arterial hypertension; chronic thromboembolic PH; connective tissue disease; systemic lupus erythematosus; mixed CTD; primary Sjögren's syndrome; idiopathic inflammatory myopathies